Status assessment of the Endangered snow leopard Panthera uncia and other large mammals in the Kyrgyz Alay, using community knowledge corrected for imperfect detection. Issue 2 (9th September 2015) - Taubmann, Julia; Sharma, Koustubh; Uulu, Kubanychbek Zhumabai; Hines, James E.; Mishra, Charudutt
Abstract: The Endangered snow leopard Panthera uncia occurs in the Central Asian Mountains, which cover c. 2 million km 2 . Little is known about its status in the Kyrgyz Alay Mountains, a relatively narrow stretch of habitat connecting the southern and northern global ranges of the species. In 2010 we gathered information on current and past (1990, the last year of the Soviet Union) distributions of snow leopards and five sympatric large mammals across 14, 000 km 2 of the Kyrgyz Alay. We interviewed 95 key informants from local communities. Across 49 400-km 2 grid cells we obtained 1, 606 and 962 records of species occurrence (site use) in 1990 and 2010, respectively. The data were analysed using the multi-season site occupancy framework to incorporate uncertainty in detection across interviewees and time periods. High probability of use by snow leopards in the past was recorded in > 70% of the Kyrgyz Alay. Between the two sampling periods 39% of sites showed a high probability of local extinction of snow leopard. We also recorded high probability of local extinction of brown bear Ursus arctos (84% of sites) and Marco Polo sheep Ovis ammon polii (47% of sites), mainly in regions used intensively by people. Data indicated a high probability of local colonization by lynx Lynx lynx in 41% of the sites. Although wildlife has declined in areas of central and eastern Alay, regions in the north-west, and the northern and southern fringes appear to retain high conservation value.